Morphological Awareness Instruction for ESL Students’ Vocabulary Development and Reading Comprehension - Aletheia Ajeng Priskinanda; Yulius Nahak; Teofanne Nurinik Wea; Barli Bram (Universitas Negeri Makassar, 2021)
This article aimed to investigate the ESL Senior High School student’s perception of Morphological Awareness Instruction and the students’ vocabulary and the significant differences of students who are trained using Morphological Awareness Instruction to enhance their reading comprehension. Two research questions were formulated, namely: First, how are the ESL Senior High School students’ understanding of the application of morphological awareness instruction to enhance their vocabulary and reading comprehension. Secondly, what are the differences of students who are trained using Morphological Awareness Instruction to enhance their vocabulary and reading comprehension with those who are not? To answer these questions, an experimental research method was implemented. The research sample consisted of 60 students of a Senior High School in Pleret, Bantul, Yogyakarta, who were selected using two phases of random sampling. The data set of questionnaires and tests were used to collect the data. The independent sample t-test was used to analyze the data. The results showed that the Morphological Awareness Instruction significantly improved students’ vocabulary skills and their reading comprehension.